FOUNDATIONS OF YOUTH LEGAL CULTURE: THEORETICAL PERSPECTIVES AND METHODOLOGICAL APPROACHES - Shodiyev Marufjon Mirsalimovich (Journal of Learning on History and Social Sciences, 2024)
This research work explores the foundational theories and methodological frameworks that underpin the study of youth legal culture. It provides a comprehensive examination of how legal culture is conceptualized within the context of youth, focusing on both theoretical perspectives and research methodologies. The study begins by detailing the key theoretical perspectives that inform our understanding of youth legal culture. It reviews major theories such as legal socialization theory, which explains how individuals acquire legal norms and values, and cultural transmission theory, which addresses how legal attitudes and behaviors are passed down through generations. The research highlights how these theories can be applied to analyze the ways in which young people interact with and perceive legal systems and norms